FAKTOR-FAKTOR YANG MEMOTIVASI NELAYAN TANGKAP DALAM BERUSAHA DI DESA LELAMO KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Jolly, Jolly; Rianse, Usman; Suriana, Suriana (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
Work motivation is a critical factor that propels fishermen in Lelamo Village to enhance their income and well-being. When motivation is high, fishermen demonstrate increased engagement in resource utilization, skill development, and innovation in addressing the challenges that impede their success. These challenges encompass various social, economic, and technical factors. The objective of this study is to ascertain the factors that motivate fishermen in Lelamo Village, Kulisusu District. The research population comprised 44 fishermen who operated fishing boats in Lelamo Village. The sample was determined using the census method. The data collection techniques employed included the use of recordings, documentation, and surveys administered via questionnaires. In addition to conducting surveys with all fishermen, the researchers conducted in-depth interviews with five key informants. The research data was analyzed using quantitative descriptive analysis. The results indicated that the primary motivations for fishermen to engage in their profession were rooted in familial and social economic needs, with a subset of fishermen also expressing personal interest and satisfaction in their occupation. Moreover, the cultural and historical legacy of Lelamo Village, the considerable potential for fishing, and the accessibility of the fishing profession are among the primary factors that influence the community's decision to pursue this occupation. The role of internal factors in the motivation of capture fishermen in Lelamo Village is of particular interest. These factors include psychological (clothing, food, shelter) and physiological (affection, self-preservation, self-strengthening) needs, which greatly influence fishermen's motivation. The majority of fishermen exhibit high levels of motivation, with a balance in the fulfillment of basic and emotional needs. This dynamic supports the welfare and productivity of capture fishermen. The role of external factors in the motivation of capture fishermen indicates that working conditions, rewards, and accountability are among the various factors that greatly influence the motivation of the community to work as capture fishermen.